Method for preparing silicon-aluminum alloy and co-producing luminescent glass from fly ash and kaolin
Through acid-soluble reaction and melting treatment of fly ash and kaolin, silicon-aluminum alloys and luminescent glass are prepared, which solves the problems of high cost and complex process for extracting alumina in the prior art, and achieves efficient utilization and industrial production.
Patent Information
- Application Number
- CN202411706911.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the process of extracting alumina from fly ash has problems such as high cost, complex process flow and difficult to industrialize.
The luminescent glass was prepared by acid-soluble reaction of fly ash with kaolin, and melting the mixture with LiBr, Al2O3, TiO2, MgO and rare earth oxides.
It realizes efficient utilization of alumina and silica in fly ash and kaolin, reduces production costs, is simple in process and can be used for industrial production, and the prepared luminescent glass has excellent performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of coal chemical technology, and in particular to a method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin. Background Art
[0002] Fly ash and slag have a special mineral phase structure characterized by mullite, corundum and glass phase. The activity of alumina is extremely poor, and it is difficult to dissolve directly with acid, alkali, etc. Most processes must pre-treat fly ash when extracting alumina. For example, lime and soda lime sintering method, calcium chloride and fluoride salt fluxing method, ammonium salt activation method, acid-base combined method, salt melting method and other process technologies all require pre-treatment of fly ash to improve the dissolution rate of alumina. Some of the above processes produce a large amount of slag (5 tons of slag are produced when one ton of fly ash is processed), some do not meet environmental protection standards, some have high costs, some are limited by equipment, and some have poor safety. It is of great significance to find an economical and feasible industrial technology route for extracting alumina from fly ash.
[0003] The prior art discloses a method for preparing aluminum silicon alloy using fly ash, comprising the steps of: subjecting a mixture containing fly ash extract to crystallization treatment in a sodium aluminate solution to form a crystalline precipitate; calcining the crystalline precipitate to obtain an electrolytic raw material having a particle size distribution of 10-30% of particles less than 45 microns, and a median particle size of 60-80 microns; subjecting the electrolytic raw material having a particle size distribution of 10-30% of particles less than 45 microns, and a median particle size of 60-80 microns to a cryolite electrolysis system with a low molecular weight ratio to prepare an aluminum silicon alloy with a low impurity content. The present invention improves the dissolution rate of aluminum silicon oxide and the utilization efficiency of fly ash, reduces the comprehensive utilization cost of fly ash, and improves production efficiency.
[0004] The prior art also discloses a method for preparing metallurgical alumina from fly ash, in which fly ash after magnetic separation to remove iron is reacted with hydrochloric acid to obtain an aluminum chloride solution, which is then deeply purified by a macroporous cationic resin to obtain a refined aluminum chloride solution, which is then concentrated, crystallized, and roasted to finally produce metallurgical alumina.
[0005] The above-mentioned technology of extracting alumina from fly ash has the problems of high cost, complicated process flow and difficulty in industrialization. Summary of the invention
[0006] The main purpose of the present application is to provide a method for preparing silicon-aluminum alloy co-produced luminescent glass using fly ash and kaolin, so as to solve the problem that fly ash cannot be efficiently utilized in the prior art.
[0007] In order to achieve the above object, according to one aspect of the present application, a method for preparing silicon-aluminum alloy co-produced luminescent glass using fly ash and kaolin is provided, comprising:
[0008] Step 1: subjecting fly ash and hydrochloric acid to an acid-soluble reaction to obtain an acid-soluble product, and subjecting the acid-soluble product to solid-liquid separation to obtain a crude liquid and filter mud;
[0009] Step 2: crystallizing the crude liquid to obtain crystalline aluminum chloride; reacting the crystalline aluminum chloride with sodium hydroxide to obtain aluminum hydroxide; mixing the aluminum hydroxide with kaolin to form a first mixture; adding coke, attapulgite and water to the first mixture to form a mass; smelting and reacting the mass to obtain an aluminum-silicon alloy melt; cooling the aluminum-silicon alloy melt to form an aluminum-silicon alloy block;
[0010] Step 3: Mix the filter mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides to form a second mixture, the second mixture is melted and cooled to obtain a glass body; the glass body is heat-treated to obtain a luminescent microcrystalline glass body.
[0011] Furthermore, the particle size of the fly ash in step 1 is less than 100 mesh.
[0012] Furthermore, before the step of subjecting the fly ash and hydrochloric acid to an acid-dissolving reaction, step 1 also includes: subjecting the fly ash to a first acid-dissolving pretreatment with hydrochloric acid to obtain pretreated fly ash; and subjecting the pretreated fly ash to an acid-dissolving reaction with hydrochloric acid to obtain an acid-dissolving product; wherein the mass concentration of the hydrochloric acid used in the first acid-dissolving pretreatment is 0.2% to 5.0%; and the mass concentration of the hydrochloric acid used in the acid-dissolving reaction is 16% to 36.4%.
[0013] Furthermore, the molar ratio of the hydrogen chloride in the hydrochloric acid used in the first acid dissolution pretreatment to the total amount of calcium oxide and magnesium oxide in the fly ash is (0.7-2):1; preferably (0.85-1):1.
[0014] Furthermore, the molar ratio of hydrogen chloride in the hydrochloric acid used in the acid dissolution reaction to aluminum oxide in the fly ash is (3-5):1; preferably (3.5-5):1.
[0015] Furthermore, the temperature of the acid dissolution reaction is 190°C to 220°C; preferably 200°C to 220°C; more preferably 200°C to 210°C.
[0016] Furthermore, the acid dissolution pretreatment time is 40 to 60 minutes.
[0017] Furthermore, the acid dissolution reaction time is 3.5 to 9.5 hours.
[0018] Furthermore, the mass concentration of the hydrochloric acid used in the first acid dissolution pretreatment is 0.5% to 2%, preferably 0.8% to 1.5%.
[0019] Furthermore, the mass concentration of the hydrochloric acid used in the acid dissolution reaction is 16% to 36.4%, preferably 20% to 31%.
[0020] Furthermore, the crude liquid in step 2 is subjected to heating evaporation and crystallization treatment to obtain crystalline aluminum chloride.
[0021] Furthermore, the heating evaporation temperature is 90°C to 130°C, and the evaporation is performed until the aluminum chloride is saturated; more preferably, the temperature is 100°C to 120°C;
[0022] Further, the crystallization process includes primary crystallization and secondary crystallization in sequence;
[0023] The process of primary crystallization includes: a crystallization temperature of 50°C to 85°C, more preferably 60°C to 80°C; a crystallization pressure of 0.01 to 0.04Mpa; more preferably 0.02 to 0.03Mpa, and an intermediate crystal product is obtained after crystallization;
[0024] The secondary crystallization process includes: dissolving the intermediate crystal product in water, the dissolution temperature is 100°C to 130°C, and more preferably 100°C to 120°C; the crystallization temperature of the secondary crystallization is 20 to 60°C, preferably 20 to 40, and crystalline aluminum chloride is obtained after crystallization.
[0025] Furthermore, the molar ratio of crystalline aluminum chloride to sodium hydroxide is 1:(2-4), the reaction temperature is 50°C-80°C, the reaction time is 1-2 hours, and the reaction product is subjected to solid-liquid separation to obtain aluminum hydroxide.
[0026] Furthermore, the kaolin is sequentially subjected to a crushing pretreatment and a second acid dissolution pretreatment to obtain pretreated kaolin.
[0027] Furthermore, the molar ratio of crystalline aluminum chloride to sodium hydroxide is 1:(2.5-3.5), and the reaction temperature is 60°C-70°C.
[0028] Furthermore, the median particle size D50 of the pretreated kaolin is 10 to 30 microns, preferably 20 to 30 microns.
[0029] Furthermore, the second acid dissolution pretreatment uses 10% to 25% and the temperature is 60 to 150°C.
[0030] Furthermore, the total content of aluminum oxide and silicon oxide in the pretreated kaolin is greater than 95%.
[0031] Furthermore, the mass ratio of aluminum oxide to silicon oxide in the pretreated kaolin is (1-1.5):1, and more preferably (1.2-1.5):1.
[0032] Furthermore, the mass ratio of aluminum oxide to silicon oxide in the first mixture is (2-2.5):1; preferably (2-2.3):1.
[0033] Furthermore, the carbon content of the coke is 85% to 100% of the total carbon content required for all reduction of the oxides; preferably 90% to 95%.
[0034] Furthermore, the added mass of attapulgite is 3% to 15% of the total mass of the first mixture; preferably 5% to 12%.
[0035] Furthermore, the agglomerates are dried to remove moisture, and then smelted and reduced to obtain an aluminum-silicon alloy melt; wherein the drying temperature is 120-150°C; the moisture content of the agglomerates after drying is less than or equal to 3%; after drying, the agglomerates are smelted and reduced in an electric arc furnace; the preferred drying temperature is 130-140°C.
[0036] Furthermore, the pressure used to make the agglomerates is 30-40 MPa, preferably 30-35 MPa.
[0037] Furthermore, the smelting temperature is 2000-2400°C; preferably 2100-2300°C.
[0038] Furthermore, the cooling process of the aluminum-silicon alloy melt includes: when the aluminum-silicon alloy melt is cooled to 1200-1400°C, the aluminum-silicon alloy melt is cast in a mold, then cooled to 700-900°C at a rate of 8-12°C / min, kept warm for 50-70 minutes, and finally naturally cooled to 20-35°C to obtain an aluminum-silicon alloy block.
[0039] Further, in step 3, the filter mud is dried to obtain dry mud; dry mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides are mixed to form a second mixture; dry mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides in the second mixture account for 60-70%, 10-20%, 5-12%, 2-8%, 1-7% and 2-5% by mass, respectively, each substance being calculated on a dry basis.
[0040] Furthermore, the rare earth oxide is Eu 2 O 3 or Tb 3 O 4 .
[0041] Furthermore, the melting treatment temperature of the second mixture is 1350-1600° C., and the melting treatment time is 2-5 hours.
[0042] Furthermore, the heat treatment process of the glass body includes primary heat treatment and secondary heat treatment; wherein, the temperature of the primary heat treatment is 500°C to 650°C, and the crystallization time is 0.5 to 2.0 hours; the temperature of the secondary heat treatment is 750°C to 880°C, and the crystallization time is 0.5 to 3.0 hours.
[0043] Furthermore, dry mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides in the second mixture account for 60-70%, 10-15%, 5-10%, 3-7%, 2-5% and 3-5% by mass respectively.
[0044] Furthermore, the melting treatment temperature of the second mixture is 1400-1530° C., and the melting treatment time is 3-4 hours.
[0045] Furthermore, the heat treatment process of the glass body includes primary heat treatment and secondary heat treatment; wherein, the temperature of the primary heat treatment is 600°C to 650°C, and the crystallization time is 0.5 to 1.0 h; the temperature of the secondary heat treatment is 750°C to 800°C, and the crystallization time is 1.5 to 2.5 h.
[0046] According to a second aspect of the present invention, there are provided silicon-aluminum alloy and luminescent glass obtained by using the above-mentioned method for preparing silicon-aluminum alloy co-producing luminescent glass with fly ash and kaolin.
[0047] Furthermore, the luminescent glass is red luminescent glass and green luminescent glass.
[0048] The technical solution of the present application provides a method for preparing aluminum-silicon alloy co-production luminescent glass by using fly ash and kaolin, and at the same time realizes the utilization of aluminum oxide and silicon oxide in fly ash and kaolin and the comprehensive utilization of white mud. The prepared luminescent glass has excellent performance, and the thermal expansion coefficient of the luminescent glass reaches 15.2 x 10 -7 ~15.9ⅹ10 -7 / ℃, the Mohs hardness of the glass reaches 8.36~8.81, and the glass density reaches 3.0~3.5g / cm 3 The luminous color is red or green; the overall process is simple, and the method can be used for industrial production with good economic benefits. DETAILED DESCRIPTION
[0049] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0050] Kaolin has good physical and chemical properties such as plasticity and fire resistance, and its mineral components are mainly composed of kaolinite, halloysite, hydromica, illite, montmorillonite, quartz, feldspar and other minerals. The present application uses kaolin and fly ash to prepare a silicon aluminum alloy and luminescent glass to improve the efficient use of fly ash.
[0051] According to one aspect of the present application, a method for preparing silicon-aluminum alloy co-produced luminescent glass using fly ash and kaolin is provided, comprising:
[0052] Step 1: subjecting fly ash and hydrochloric acid to an acid-soluble reaction to obtain an acid-soluble product, and subjecting the acid-soluble product to solid-liquid separation to obtain a crude liquid and filter mud;
[0053] Step 2: crystallizing the crude liquid to obtain crystalline aluminum chloride; reacting the crystalline aluminum chloride with sodium hydroxide to obtain aluminum hydroxide; mixing the aluminum hydroxide with kaolin to form a first mixture; adding coke, attapulgite and water to the first mixture to form a mass; smelting and reacting the mass to obtain an aluminum-silicon alloy melt; cooling the aluminum-silicon alloy melt to form an aluminum-silicon alloy block;
[0054] Step 3: Mix the filter mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides to form a second mixture, the second mixture is melted and cooled to obtain a glass body; the glass body is heat-treated to obtain a luminescent microcrystalline glass body.
[0055] The present application discloses a method for preparing aluminum-silicon alloy co-produced luminescent glass using fly ash and kaolin, which simultaneously realizes the utilization of aluminum oxide and silicon oxide in fly ash and kaolin and the comprehensive utilization of white mud. The prepared luminescent glass has excellent performance and a simple process. The method can be used for industrial production and has good economic benefits.
[0056] In some embodiments, the particle size of the fly ash in step 1 is less than 100 mesh; the fly ash is first subjected to a first acid dissolution pretreatment with a first hydrochloric acid to obtain pretreated fly ash; the pretreated fly ash is then subjected to an acid dissolution reaction with a second hydrochloric acid to obtain an acid-soluble product; wherein the concentration of the first hydrochloric acid is 0.2% to 5.0%; the concentration of the second hydrochloric acid is 16% to 36.4%; for example, 16%, 18%, 20%, 22, 25%, 28%, 30%, 32%, 35%, 36.4%.
[0057] The present application crushes the fly ash to less than 100 mesh (it can also pass through a 100 mesh standard sieve), and then pre-treats the crushed fly ash with dilute hydrochloric acid (first hydrochloric acid) to cause the calcium and magnesium oxides to be initially reacted and consumed, which is beneficial to promote the subsequent dissolution treatment of alumina in the fly ash, and the hydrochloric acid consumption is small.
[0058] In some embodiments, the molar ratio of the hydrogen chloride in the first hydrochloric acid to the total amount of calcium oxide and magnesium oxide in the fly ash is (0.7-2):1; preferably (0.85-1):1, for example 0.9:1; the concentration of the first hydrochloric acid is preferably 0.5%-2%, more preferably 0.8%-1.5%, for example 0.8%, 1.0% or 1.5%. The present application adopts the above-mentioned concentration of dilute hydrochloric acid and the molar ratio of dilute hydrochloric acid to the total amount of calcium oxide and magnesium oxide, which can fully remove calcium oxide and magnesium oxide in fly ash without affecting aluminum oxide in fly ash. In addition, those skilled in the art can also understand that the fly ash raw material used can also include slag with larger particles.
[0059] In some embodiments, the molar ratio of hydrogen chloride in the second hydrochloric acid to alumina in the fly ash is (3-5):1; for example, the molar ratio of the acid dissolution reaction can be selected from any value of 3, 3.5, 4, 4.5, 5, or any range between two values; preferably (3.5-5):1; the temperature of the acid dissolution reaction is 190°C to 220°C; for example, the reaction temperature can be selected from any value of 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, or any range between two values. ; preferably 200℃~220℃; more preferably 200℃~210℃; for example 202℃ or 210℃; the concentration of the second hydrochloric acid is preferably 16%~36.4%; for example, it can be selected from any value of 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36.5 or any range between two values; more preferably 20%~31%, for example 25%. The time of acid dissolution pretreatment is 40~60min, the temperature of acid dissolution pretreatment is room temperature 20~35℃, and the time of acid dissolution reaction is 3.5~9.5h.
[0060] The present application adopts the above-mentioned concentration of the second hydrochloric acid, the molar ratio of hydrochloric acid to alumina, and the reaction temperature, and makes full use of hydrochloric acid to carry out alumina dissolution reaction on the pretreated product, and further reacts the alumina in the fly ash with the hydrochloric acid to generate the target product aluminum chloride. It is understood by those skilled in the art that the acid dissolution time will also affect the dissolution effect of alumina or other oxides, so the acid dissolution time is usually suitable for dissolving the target alumina as much as possible while considering the time cost, such as 3-10 hours.
[0061] The present application separates the acid-soluble product into solid and liquid to obtain crude liquid and filter mud for subsequent recycling.
[0062] In some embodiments, the crude liquid in step 2 is subjected to heating evaporation and crystallization treatment to obtain crystalline aluminum chloride. In order to further improve the purity, recrystallization treatment can also be performed. The heating evaporation temperature is 90°C to 130°C, and the aluminum chloride is evaporated to saturation; it can be selected from any value of 90°C, 100°C, 110°C, 120°C, 130°C or any range between the two; more preferably 100°C to 120°C; for example, 100°C or 120°C.
[0063] The crystallization process includes primary crystallization and secondary crystallization; wherein the temperature of the primary crystallization treatment is 50°C to 85°C; it can be selected from any value of 50°C, 60°C, 70°C, 80°C, 85°C or any range between the two; further preferably 60°C to 80°C; for example, 60°C or 80°C; the pressure of the crystallization treatment is 0.01 to 0.04Mpa; further preferably 0.02 to 0.03Mpa; an intermediate crystallization product is obtained; the secondary crystallization process includes: dissolving the intermediate crystallization product (that is, the crude crystalline aluminum chloride of the first crystallization product) in water, the dissolution temperature is 100°C to 130°C, preferably 100°C to 120°C, for example, 110°C; the temperature of the recrystallization of the dissolved aluminum chloride is 20 to 60°C, preferably 20 to 40°C, for example, 30°C, to obtain the above-mentioned crystalline aluminum chloride. The present application adopts the above-mentioned heating evaporation temperature to remove the moisture and other volatile substances in the crude liquid as much as possible, so as to achieve the purpose of purifying aluminum chloride, and then crystallizes at the above-mentioned temperature to make the aluminum chloride fully crystallized and extracted.
[0064] In some embodiments, the molar ratio of crystalline aluminum chloride and sodium hydroxide is 1: (2-4), the reaction temperature is 50°C-80°C, the reaction time is 1-2 hours, and the reaction product is subjected to solid-liquid separation to obtain aluminum hydroxide. The above molar ratio can be selected from any value of 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any range between the two; the reaction ratio is preferably 1: (2.5-3.5), for example 1:3; the reaction temperature is selected from any value of 50°C, 60°C, 70°C, 80°C or any range between the two; preferably 60-70°C. The present application adopts the above reaction ratio and matching reaction temperature to make the crystalline aluminum chloride and sodium hydroxide react fully to obtain as much aluminum hydroxide as possible.
[0065] In some embodiments, kaolin is subjected to crushing pretreatment and second acid dissolution pretreatment in sequence to obtain pretreated kaolin. The median particle size D50 of the crushed kaolin is 10 to 30 microns, preferably 20 to 30 microns, which is beneficial to the reaction rate. The mass concentration of hydrochloric acid used in the second acid dissolution pretreatment is 10% to 25%, and the temperature is 60 to 150°C; for example, the hydrochloric acid concentration is 20% and the temperature is 100°C; the total content of aluminum oxide and silicon oxide in the kaolin after the second acid dissolution pretreatment is greater than 95%.
[0066] The present application crushes kaolin to facilitate the subsequent acid dissolution to remove impurities such as iron, potassium and sodium in kaolin, thereby obtaining a relatively pure mixture of aluminum oxide and silicon oxide, the content of which is greater than 95%, and the mass ratio of aluminum oxide to silicon oxide is (1 to 1.5): 1, and more preferably (1.2 to 1.5): 1. The aluminum-silicon ratio in the final product is controlled by regulating the ratio of these two substances.
[0067] In some embodiments, aluminum hydroxide, aluminum oxide and silicon oxide are mixed to form a first mixture; the mass ratio of aluminum oxide to silicon oxide in the prepared first mixture is (2-2.5):1; preferably (2-2.3):1. Based on the first mixture, coke carbon is added thereto as a reducing agent; wherein the content of the added coke is expressed by its total carbon content, and the carbon content of the coke is 85% to 100% of the total carbon required for the oxide (the oxide includes the main components of aluminum oxide, silicon oxide, a small amount of magnesium oxide, iron oxide, and a trace amount of other metal oxides) to be completely reduced (completely reacted); preferably 90% to 95%, such as 85%, 90%, 95%, 100%; the added mass of the attapulgite binder is 3% to 15% of the total mass of the first mixture; preferably 5% to 12%, such as any value among 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or any range between two values; the amount of water added is sufficient to form a mass of the mixture.
[0068] In some embodiments, the pressure used to make the agglomerates is 30-40 MPa, preferably 30-35 MPa. The formed agglomerates are then dried to remove moisture, and then smelted and reduced to obtain an aluminum-silicon alloy melt. The drying temperature is 120-150°C, for example 120°C, 130°C, 140°C, 150°C, preferably 130-140°C, and the water content of the agglomerates after drying is less than or equal to 3%.
[0069] In some embodiments, after the agglomerate is dried, it is melted and reduced in an electric arc furnace; the melting temperature is 2000-2400°C; it can be any value among 2000°C, 2100°C, 2200°C, 2300°C, 2400°C or any range between two values; preferably 2100-2300°C; when the aluminum-silicon alloy melt is cooled to 1200-1400°C (for example, 1200°C, 1300°C, 1400°C), the aluminum-silicon alloy melt is cast in a mold, and then cooled to 700-900°C (for example, 700°C, 800°C, 900°C) at 8-12°C / min (for example, 8, 9, 10, 11, 12°C / min), kept warm for 50-70min (for example, 50, 60, 70min), and finally naturally cooled to 20-35°C (normal temperature) to obtain an aluminum-silicon alloy block. The present application adopts the above-mentioned melting temperature, cooling rate, and holding time to fully melt the silicon, aluminum, and iron elements and form an aluminum-silicon alloy with a relatively high purity.
[0070] In some embodiments, in step 3, the filter mud (white mud) is dried to obtain dry mud; dry mud, LiBr, Al 2 O 3 、TiO 2 , MgO and rare earth oxides are mixed to form a second mixture; dry white mud, LiBr, Al 2 O 3 、TiO 2 The mass proportions of MgO and rare earth oxides in the second mixture are 60-70%, 10-20%, 5-12%, 2-8%, 1-7% and 2-5% respectively, and the total amount of each substance is 100% on a dry basis; wherein the mass proportion of white mud in the second mixture is selected from any value of 60%, 62%, 65%, 68%, 70% or a range between any two of them; the mass proportion of LiBr in the second mixture is selected from any value of 10, 12%, 15%, 18%, 20% or a range between any two of them; Al 2 O 3 The mass proportion in the second mixture is selected from any value among 5%, 8%, 10%, 12%, or any range between the two; TiO 2 The mass proportion in the second mixture is selected from any value among 2%, 5%, 6%, 8% or any range between the two; the mass proportion of MgO in the second mixture is selected from any value among 1%, 3%, 5%, 7% or any range between the two; the mass proportion of rare earth oxide in the second mixture is selected from any value among 2%, 3%, 4%, 5% or any range between the two; further preferably, dry mud, LiBr, Al 2 O 3 、TiO 2, MgO and rare earth oxides in the second mixture account for 60-70%, 10-15%, 5-10%, 3-7%, 2-5% and 3-5% by mass, respectively. 2 O 3 、TiO 2 , MgO, and rare earth oxides are mixed as glass components and the mass ratio of each component is matched. After melting treatment, a glass body with good hardness and density can be obtained.
[0071] In some embodiments, the rare earth oxide is Eu 2 O 3 or Tb 3 O 4 This application adds Eu to the glass component 2 O 3 , can make the glass emit red light, adding Tb 3 O 4 The glass body can emit green light; other substances with luminescent properties can also be selected and added to the glass components to obtain glass bodies with different luminescent colors.
[0072] In some embodiments, the melting temperature of the second mixture is 1350-1600°C, and the melting time is 2-5 hours; preferably 1400-1530°C, 3-4 hours; the melting temperature can be selected from any value of 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, or a range between any two of them; the melting time can be selected from any value of 2h, 3h, 4h, 5h, or a range between any two of them. The present application can fully and evenly melt and mix the glass bodies at the above melting temperatures, which is conducive to forming a glass body with good hardness and density.
[0073] In some embodiments, the heat treatment process of the glass body includes primary heat treatment and secondary heat treatment; the temperature of the primary heat treatment is 500°C to 650°C, and the crystallization time is 0.5 to 2.0 h, which can be selected from any value of 500°C, 520°C, 550°C, 580°C, 600°C, 630°C, 650°C or any range between two of them; the time is selected from any value of 0.5h, 1h, 1.5h, 2.0h or any range between two of them. The temperature of the secondary heat treatment is 750℃~880℃, the crystallization time is 0.5~3.0h, which can be selected from any value of 750℃, 780℃, 800℃, 820℃, 850℃, 880℃ or any range between two values, and the time is selected from any value of 0.5h, 1h, 1.5h, 2.0h, 2.3h, 2.5h, 2.8h, 3.0h or any range between two values; further preferably, the temperature of the primary heat treatment is 600℃~650℃, and the crystallization time is 0.5~1.0h; further preferably, the temperature of the secondary heat treatment is 750℃~800℃, and the crystallization time is 1.5~2.5h. The present application can further improve the performance of the glass by two heat treatments.
[0074] According to a second aspect of the present invention, there is provided a silicon-aluminum alloy and a luminescent glass obtained by using the above-mentioned method of preparing silicon-aluminum alloy co-production luminescent glass with fly ash and kaolin; the thermal expansion coefficient of the luminescent glass reaches 15.2 x 10 -7 ~15.9ⅹ10 -7 / ℃, the Mohs hardness of the glass reaches 8.36~8.81, and the glass density reaches 3.0~3.5g / cm 3 , the luminous color is red or green.
[0075] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0076] Unless otherwise specified, the contents described in this application are all by mass.
[0077] The fly ash used in the following examples of the present application is a by-product produced by coal used in power plants. The main components and contents are shown in Table 1.
[0078] Example 1
[0079] (1) Weigh one kilogram of fly ash (the components are shown in Table 1) and grind it to less than 100 meshes, and add a first hydrochloric acid at room temperature for acid dissolution pretreatment to remove calcium oxide and magnesium oxide in the fly ash to obtain a pretreated material; wherein the molar ratio of the first hydrochloric acid to the total amount of calcium oxide and magnesium oxide in the fly ash is 0.85:1; the concentration of the first hydrochloric acid is 0.5%; the reaction time is 50 minutes; and the stirring speed is 100 revolutions per minute.
[0080] (2) reacting the pretreated material in step (1) and the second hydrochloric acid in a high-temperature reactor to obtain an acid-soluble product; wherein the molar ratio of hydrochloric acid to alumina in fly ash is 3.5:1; the mass concentration of the second hydrochloric acid is 16.5%; the reaction time is 9 hours; the reaction temperature is 200°C; and the stirring speed is 100 rpm.
[0081] (3) After the reaction in step (2) is completed, the acid-soluble product is subjected to solid-liquid separation and washing to obtain a crude liquid and white mud.
[0082] (4) heating the crude liquid of step (3) for evaporation and crystallization to obtain crystalline aluminum chloride; wherein the heating evaporation temperature is controlled at 110° C.; the crystallizer temperature is controlled at 65° C.; and the crystallization pressure is controlled at 0.01 MPa; after the crystallization treatment is completed, solid-liquid separation and washing are performed to obtain crystalline aluminum chloride; then the crystalline aluminum chloride is heated again in water to dissolve, and finally the aluminum chloride solution is cooled for recrystallization to obtain crystalline aluminum chloride with higher purity; wherein the recrystallization temperature is 40° C.
[0083] (5) adding sodium hydroxide to the crystallized aluminum chloride of step (4) to react to obtain aluminum hydroxide; wherein the molar ratio of the crystallized aluminum chloride to the sodium hydroxide is 1:3, the reaction is stirred for 2 hours, the reaction temperature is 80° C., and then the solid-liquid separation is performed to obtain an aluminum hydroxide product.
[0084] (6) crushing one kilogram of kaolin (components shown in Table 2) to a particle size of D50 = 20 microns, mixing the pretreated kaolin material with a third hydrochloric acid for acid dissolution, removing iron, potassium and sodium impurities, and obtaining a mixture of aluminum oxide and silicon oxide; wherein the concentration of the third hydrochloric acid is 15%; the total weight content of aluminum oxide and silicon oxide in the mixture is greater than 95%, and the weight ratio of aluminum oxide to silicon oxide is 1:1;
[0085] (7) The aluminum hydroxide extracted in step (5) and the mixture of aluminum oxide and silicon oxide in step (6) are mixed in a mass ratio of aluminum oxide to silicon oxide of 2:1 to form a first mixture.
[0086] (8) adding coke as a carbonaceous reducing agent to the first mixture, wherein the carbon content of the coke is 90% of the total carbon content required for the complete reaction of oxides (mainly aluminum oxide, silicon oxide and a small amount of magnesium oxide, iron oxide and trace metal oxides) with carbon; then adding attapulgite and water to the first mixture, mixing evenly and forming pellets, wherein the mass of attapulgite added is 10% of the total amount of the first mixture in step (7), the pelletizing pressure is 40 MPa, the pellet drying temperature is 120°C, and the moisture content of the pellets after drying is not more than 3%.
[0087] (9) The dried agglomerates of step (8) are melted in an electric arc furnace at a melting temperature of 2100°C to obtain an aluminum-silicon alloy melt. When the temperature of the molten body is reduced to 1300°C, it is cast in a mold, and then the temperature is reduced to 800°C at 10°C / min, and the temperature is kept at this temperature for 60 minutes. After naturally cooling to room temperature, an aluminum-silicon alloy is obtained.
[0088] (10) The dried white mud of step (3) is mixed with LiBr and an appropriate amount of Al 2 O 3 、TiO 2 、MgO、Eu 2 O 3 The ingredients are mixed in a certain mass ratio to form a second mixture; wherein m (dry white mud), m (Al 2 O 3 )、m(LiBr)、m(TiO 2 )、m(MgO)、m(Eu 2 O 3 ) are 63%, 15%, 10%, 7%, 3% and 2% respectively.
[0089] (11) The second mixed material of step (10) is placed in a platinum crucible at a melting temperature of 1500° C. for 2 h. After melting, the crucible is taken out, and a glass cylinder is obtained by casting, and the glass body is obtained by cooling for 1 h.
[0090] (12) The glass body of step (11) was placed in a muffle furnace for a primary heat treatment at a temperature of 600° C. and a crystallization time of 1.0 h; a secondary heat treatment temperature of 780° C. and a crystallization time of 1.5 h to obtain a luminescent glass product. See Table 3 for details.
[0091] Example 2
[0092] The difference between Example 2 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3 Different addition amounts (Eu 2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0093] Example 3
[0094] The difference between Example 3 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3Different addition amounts (Eu 2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0095] Example 4
[0096] The difference between Example 4 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3 Different addition amounts (Eu 2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0097] Example 5
[0098] The difference between Example 5 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3 Different addition amounts (Eu 2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0099] Example 6
[0100] The difference between Example 6 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3 Different addition amounts (Eu 2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0101] Example 7
[0102] The difference between Example 7 and Example 1 is that the acid dissolution reaction temperature is different, the mass ratio of alumina and silicon oxide after kaolin acid dissolution pretreatment is different, the melting temperature of the dried agglomerate is different, and Eu 2 O 3 Different addition amounts (Eu2 O 3 The change in amount is made up with the amount of white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different compositions, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 3 for details.
[0103] Table 1
[0104] Element <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[P 2 THE 5 ]]> LOI total unit content 41.58 45.92 1.77 2.31 1.24 2.60 0.39 0.09 0.00 4.05 100 %
[0105] Table 2
[0106] Element <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[TiO 2 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[P 2 THE 5 ]]> LOI total unit content 29.252 45.4 3.423 1.432 0.08 1.627 0.353 0.320 0.00 18.12 100 %
[0107] Table 3
[0108]
[0109] Example 8
[0110] (1) Weigh one kilogram of fly ash (components shown in Table 1) and grind it to less than 100 mesh; add a first hydrochloric acid at room temperature for acid dissolution pretreatment to remove calcium oxide and magnesium oxide in the fly ash to obtain a pretreated material; wherein the molar ratio of the first hydrochloric acid to calcium oxide and magnesium oxide in the fly ash is 0.85:1; the concentration of the first hydrochloric acid is 0.5%; the reaction time is 50 minutes; and the stirring speed is 100 revolutions per minute.
[0111] (2) reacting the pretreated material in step (1) and the second hydrochloric acid in a high-temperature reactor to obtain an acid-soluble product; wherein the molar ratio of hydrochloric acid to alumina in fly ash is 3.5:1; the concentration of the second hydrochloric acid is 36.4%; the reaction time is 3.5 h; the reaction temperature is 200° C.; and the stirring speed is 100 rpm.
[0112] (3) After the reaction in step (2) is completed, the acid-soluble product is subjected to solid-liquid separation and washing to obtain a crude liquid and white mud.
[0113] (4) heating the crude liquid of step (3) for evaporation and crystallization to obtain crystalline aluminum chloride; wherein the heating evaporation temperature is controlled at 110° C.; the crystallizer temperature is controlled at 65° C.; and the crystallization pressure is controlled at 0.01 MPa; after the crystallization treatment is completed, solid-liquid separation and washing are performed to obtain crystalline aluminum chloride; then the crystalline aluminum chloride is heated again in water to dissolve, and finally the aluminum chloride solution is cooled for recrystallization to obtain crystalline aluminum chloride with higher purity; wherein the recrystallization temperature is 40° C.
[0114] (5) adding sodium hydroxide to the crystallized aluminum chloride of step (4) to react to obtain aluminum hydroxide; wherein the molar ratio of the crystallized aluminum chloride to the sodium hydroxide is 1:3, the reaction is stirred for 2 hours, the reaction temperature is 80° C., and then the solid-liquid separation is performed to obtain an aluminum hydroxide product.
[0115] (6) One kilogram of kaolin (components are shown in Table 2) is crushed and pre-treated to a particle size of D50 = 30 microns, and the pre-treated kaolin material is mixed with a third hydrochloric acid for acid dissolution to remove iron, potassium and sodium impurities to obtain a mixture of aluminum oxide and silicon oxide; wherein the concentration of the third hydrochloric acid is 18%; the total mass content of aluminum oxide and silicon oxide in the mixture is greater than 95%, and the mass ratio of aluminum oxide to silicon oxide is 1.5:1.
[0116] (7) The aluminum hydroxide extracted in step (5) and the mixture of aluminum oxide and silicon oxide in step (6) are mixed in a mass ratio of aluminum oxide to silicon oxide of 2:1 to form a first mixture.
[0117] (8) Adding a carbonaceous reducing agent of coke to the first mixture, wherein the carbon content of the coke is 95% of the total carbon content required for the complete reaction of oxides (mainly aluminum oxide, silicon oxide and a small amount of magnesium oxide, iron oxide and trace metal oxides) with carbon; then adding attapulgite and water to the first mixture, mixing evenly and forming pellets, wherein the mass of attapulgite added is 10% of the total amount of the first mixture in step (7), the pelletizing pressure is 40 MPa, the pellet drying temperature is 120°C, and the moisture content of the pellets after drying is not more than 3%.
[0118] (9) The dried agglomerates of step (8) are melted in an electric arc furnace at a melting temperature of 2100-2300°C to obtain an aluminum silicon alloy melt. When the melt is cooled to 1300°C, it is cast in a mold, and then cooled to 900°C at 6°C / min, kept at this temperature for 30 minutes, and naturally cooled to room temperature to obtain an aluminum silicon alloy.
[0119] (10) The dried white mud of step (3) is mixed with LiBr and an appropriate amount of Al 2 O 3 、TiO 2 、MgO、Eu 2 O 3 The ingredients are mixed in a certain mass ratio to form a second mixture; wherein m (dry white mud), m (Al 2 O 3 )、m(LiBr)、m(TiO 2 )、m(MgO)、m(Tb 3 O 4) They are 63%, 15%, 10%, 7%, 3% and 2% respectively.
[0120] (11) The second mixed material of step (10) is placed in a platinum crucible at a melting temperature of 1500° C. for 2 h. After melting, the crucible is taken out, and a glass cylinder is obtained by casting, and the glass body is obtained by cooling for 1 h.
[0121] (12) The glass body of step (11) was placed in a muffle furnace for a primary heat treatment at a temperature of 600° C. and a crystallization time of 1.0 h; a secondary heat treatment temperature of 780° C. and a crystallization time of 1.5 h to obtain a luminescent glass product. See Table 3 for details.
[0122] Example 9
[0123] The difference between Example 9 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of the coke reducing agent is different, the smelting temperature of the dried agglomerate is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0124] Example 10
[0125] The difference between Example 10 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of the coke reducing agent is different, the smelting temperature of the dried agglomerate is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0126] Embodiment 11
[0127] The difference between Example 11 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of the coke reducing agent is different, the smelting temperature of the dried agglomerate is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0128] Example 12
[0129] The difference between Example 12 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of coke reducing agent is different, the smelting temperature of drying agglomerates is different, Tb 3 O 4 Different addition amounts (Tb 3 O 4The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0130] Embodiment 13
[0131] The difference between Example 13 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of the coke reducing agent is different, the smelting temperature of the dried agglomerate is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0132] Embodiment 14
[0133] The difference between Example 14 and Example 8 is that the particle size of kaolin after pretreatment is different, the carbon content of coke reducing agent is different, the smelting temperature of drying agglomerates is different, Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared silicon-aluminum-iron alloy has different components, and the prepared luminescent glass has different properties; the other preparation processes are the same as those in Example 1; see Table 4 for details.
[0134] Table 4
[0135]
[0136]
[0137] The Al / Si / Mg composition of the alloy in Table 3 and Table 4 of the present application also includes other trace elements.
[0138] Comparative Example 1
[0139] (1) Weigh one kilogram of fly ash and grind it to less than 100 mesh; the molar ratio of hydrochloric acid to calcium oxide and magnesium oxide in fly ash is 0.85:1; the concentration of hydrochloric acid is 0.5%; the reaction time is 50 minutes; the stirring speed is 100 revolutions per minute.
[0140] (2) reacting the pretreated material with hydrochloric acid in a high-temperature reactor, wherein the molar ratio of hydrochloric acid to alumina in fly ash is 3.5:1; the concentration of hydrochloric acid is 16.1%; the reaction time is 9.5 h; the reaction temperature is 100° C.; and the stirring speed is 100 rpm.
[0141] (3) After the reaction is completed, solid-liquid separation and washing are carried out to obtain crude liquid and white mud.
[0142] (4) Evaporation crystallization control temperature: 110°C; crystallizer temperature control: 65°C; pressure control: 0.01Mpa; after the reaction is completed, solid-liquid separation and washing are performed to obtain crystalline aluminum chloride. Then, it is heated again to dissolve in water, and cooled to recrystallize the aluminum chloride solution, and the recrystallization temperature is: 40°C.
[0143] (5) Sodium hydroxide was added to the crystalline aluminum chloride at a molar ratio of 1:3, and the mixture was stirred for 2 hours at a reaction temperature of 80° C., followed by solid-liquid separation to obtain an aluminum hydroxide product.
[0144] (6) crushing one kilogram of kaolin for pretreatment to a particle size of D50 = 10-30 microns, mixing the pretreated material with hydrochloric acid (mass concentration is 1%) for acid dissolution to remove iron, potassium and sodium impurities, and obtaining a mixture of aluminum oxide and silicon oxide, wherein the mass content of aluminum oxide and silicon oxide is greater than 95%; the mass ratio of aluminum oxide to silicon oxide is 1.5:1.
[0145] (7) Aluminum hydroxide is mixed with aluminum oxide and silicon oxide so that the mass ratio of aluminum oxide to silicon oxide is 2:1.
[0146] (8) The carbon content of the coke carbonaceous reducing agent added to the material with a certain aluminum-silicon ratio is 50% of the carbon content required for the complete reaction of the metal oxide and carbon. The attapulgite and water are evenly mixed and then pelletized. The mass of the attapulgite added is 10% of the amount of the mixed material. The pelletizing pressure is 40 MPa, the pellet drying temperature is 120°C, and the moisture content of the pellets after drying is not more than 3%.
[0147] (9) The molten material is melted in an electric arc furnace at a melting temperature of 1500°C to obtain an aluminum-silicon alloy melt. When the temperature of the molten material drops to 1300°C, the molten material is cast in a mold, and then the temperature is dropped to 900°C at 6°C / min, and the temperature is kept at this temperature for 30 minutes. After cooling to room temperature, an aluminum-silicon alloy is obtained.
[0148] (10) Dried white mud, LiBr and appropriate amount of Al 2 O 3 、TiO 2 、MgO、Tb 3 O 4 Mix the ingredients in a certain ratio. Among them, m (dry white mud), m (Al 2 O 3 )、m(LiBr)、m(TiO 2 )、m(MgO)、m(Tb 3 O 4) They are 69.5%, 15%, 10%, 7%, 3% and 0.5% respectively.
[0149] (11) The mixed material is placed in a platinum crucible at a melting temperature of 1500°C for 2 h. After melting, the crucible is removed and a glass cylinder is obtained by casting, and the mixture is cooled for 1 h.
[0150] (12) The glass was placed in a muffle furnace for heat treatment at a temperature of 600°C and a crystallization time of 1.0 h. The glass was subjected to a second heat treatment at a temperature of 780°C and a crystallization time of 1.5 h to obtain a luminescent glass product.
[0151] Comparative Example 2
[0152] The difference between Comparative Example 2 and Comparative Example 1 is that the acid dissolution reaction temperature is different, the coke content is different, the agglomerate melting temperature is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared aluminum-silicon alloy components are different, and the prepared glass properties are different.
[0153] Comparative Example 3
[0154] The difference between Comparative Example 3 and Comparative Example 1 is that the acid dissolution reaction temperature is different, the coke content is different, the agglomerate melting temperature is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared aluminum-silicon alloy components are different, and the prepared glass properties are different.
[0155] Comparative Example 4
[0156] The difference between Comparative Example 4 and Comparative Example 1 is that the acid dissolution reaction temperature is different, the coke content is different, the agglomerate melting temperature is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared aluminum-silicon alloy components are different, and the prepared glass properties are different.
[0157] Comparative Example 5
[0158] The difference between Comparative Example 5 and Comparative Example 1 is that the acid dissolution reaction temperature is different, the coke content is different, the agglomerate melting temperature is different, and Tb 3 O 4 Different addition amounts (Tb 3 O 4 The change in amount is made up by white mud, totaling 100%), the prepared aluminum-silicon alloy components are different, and the prepared glass properties are different.
[0159] Table 5
[0160]
[0161]
[0162] The experimental data in Table 3 of Examples 1 to 7 of the present application and the experimental data in Table 4 of Examples 8 to 14 show that the aluminum content in the aluminum-silicon alloy prepared by the preparation method designed in the present application, especially the acid dissolution reaction temperature of fly ash and hydrochloric acid, the mass ratio of aluminum oxide to silicon oxide after acid dissolution of kaolin, the smelting temperature of the agglomerate, and the addition amount of rare earth oxide in the agglomerate, can reach more than 91% and the thermal expansion coefficient of the prepared luminescent glass can reach 15.2 x 10 -7 ~15.9ⅹ10 -7 / ℃, the Mohs hardness of the glass reaches 8.36~8.81, and the glass density reaches 3.0~3.5g / cm 3 , the luminous color is red or green.
[0163] Comparative Examples 1 to 5 adopt the preparation process of the present application, but due to unreasonable control of key process parameters, especially the acid dissolution reaction temperature is too low, such as 100-140°C, the carbon content of the coke reducing agent added to the kaolin is too low, such as 50%-75%, the agglomerate smelting temperature is too low, such as 1500-1900°C, Tb 3 O 4 If the addition amount is too low, such as 0.5-1.0%, the prepared aluminum-silicon alloy will be of poor quality, with a high impurity content, and will be difficult to alloy. The prepared glass will not emit light, and the glass hardness and glass density will be inferior to the glass properties of the embodiments of the present application.
[0164] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0165] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing silicon-aluminum alloy co-production luminescent glass using fly ash and kaolin, characterized in that: The method comprises: Step 1: subjecting fly ash and hydrochloric acid to an acid-soluble reaction to obtain an acid-soluble product, and subjecting the acid-soluble product to solid-liquid separation to obtain a crude liquid and filter mud; Step 2: crystallizing the crude liquid to obtain crystallized aluminum chloride; reacting the crystallized aluminum chloride with sodium hydroxide to obtain aluminum hydroxide; mixing the aluminum hydroxide with kaolin to form a first mixture; adding coke, attapulgite and water to the first mixture to form a mass; smelting and reacting the mass to obtain an aluminum-silicon alloy melt; cooling the aluminum-silicon alloy melt to form an aluminum-silicon alloy block; Step 3: Mix the filter mud, LiBr, Al2O3, TiO2, MgO and rare earth oxides to form a second mixture, melt the second mixture, cool it to obtain a glass body; heat-treat the glass body to obtain a luminescent microcrystalline glass body.
2. The method for preparing silicon-aluminum alloy co-production luminescent glass by using fly ash and kaolin according to claim 1, characterized in that: The particle size of the fly ash in step 1 is less than 100 mesh; And / or, before the step of subjecting the fly ash and the hydrochloric acid to the acid dissolution reaction, the step 1 also includes: subjecting the fly ash to a first acid dissolution pretreatment with hydrochloric acid to obtain pretreated fly ash; subjecting the pretreated fly ash to the acid dissolution reaction with hydrochloric acid to obtain the acid-soluble product; wherein the mass concentration of the hydrochloric acid used in the first acid dissolution pretreatment is 0.2% to 5.0%; and the mass concentration of the hydrochloric acid used in the acid dissolution reaction is 16% to 36.4%.
3. The method for preparing silicon-aluminum alloy co-production luminescent glass by using fly ash and kaolin according to claim 2, characterized in that: The molar ratio of the hydrogen chloride in the hydrochloric acid used in the first acid dissolution pretreatment to the total amount of calcium oxide and magnesium oxide in the fly ash is (0.7-2):1; preferably (0.85-1):1; And / or, the molar ratio of hydrogen chloride in the hydrochloric acid used in the acid dissolution reaction to the aluminum oxide in the fly ash is (3-5):1; preferably (3.5-5):1; And / or, the temperature of the acid dissolution reaction is 190°C to 220°C; preferably 200°C to 220°C; more preferably 200°C to 210°C; And / or, the first acid dissolution pretreatment time is 40 to 60 minutes; And / or, the acid dissolution reaction time is 3.5 to 9.5 hours; And / or, the mass concentration of hydrochloric acid used in the first acid dissolution pretreatment is 0.5% to 2%; preferably 0.8% to 1.5%; And / or, the mass concentration of hydrochloric acid used in the acid dissolution reaction is 16% to 36.4%; preferably 20% to 31%.
4. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to any one of claims 1 to 3, characterized in that: The crude liquid in step 2 is subjected to heating evaporation and crystallization treatment to obtain the crystalline aluminum chloride; Preferably, the heating evaporation temperature is 90°C to 130°C, and the evaporation is performed until the aluminum chloride is saturated; more preferably, the heating evaporation temperature is 100°C to 120°C; Preferably, the crystallization process includes primary crystallization and secondary crystallization in sequence; The process of the primary crystallization comprises: a crystallization temperature of 50°C to 85°C, more preferably 60°C to 80°C; a crystallization pressure of 0.01 to 0.04Mpa; more preferably 0.02 to 0.03Mpa, and an intermediate crystal product is obtained after crystallization; The secondary crystallization process comprises: dissolving the intermediate crystal product in water, the dissolution temperature is 100°C to 130°C, more preferably 100°C to 120°C; the crystallization temperature of the secondary crystallization is 20 to 60°C, preferably 20 to 40, and the crystalline aluminum chloride is obtained after crystallization.
5. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to any one of claims 1 to 4, characterized in that: The molar ratio of the crystalline aluminum chloride to the sodium hydroxide is 1:(2-4), the reaction temperature is 50° C.-80° C., the reaction time is 1-2 hours, and the reaction product is subjected to solid-liquid separation to obtain the aluminum hydroxide; And / or, the kaolin is subjected to a crushing pretreatment and a second acid dissolution pretreatment in sequence to obtain pretreated kaolin.
6. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to claim 5, characterized in that: The molar ratio of the crystalline aluminum chloride to the sodium hydroxide is 1:(2.5-3.5), and the reaction temperature is 60° C.-70° C.; And / or, the median particle size D50 of the kaolin after the crushing pretreatment is 10 to 30 microns; preferably 20 to 30 microns; And / or, the hydrochloric acid mass concentration used in the second acid dissolution pretreatment is 10% to 25% and the temperature is 60 to 150° C.; and / or, the total content of alumina and silica in the pretreated kaolin is greater than 95%; And / or, the mass ratio of the aluminum oxide to the silicon oxide in the pretreated kaolin is (1-1.5):1, and more preferably (1.2-1.5):
1.
7. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to any one of claims 1 to 6, characterized in that: The mass ratio of aluminum oxide to silicon oxide in the first mixture is (2-2.5):1; preferably (2-2.3):1; and / or, the carbon content of the coke is 85% to 100% of the total carbon content required for all reduction of the oxides; preferably 90% to 95%; And / or, the added mass of the attapulgite is 3% to 15% of the total mass of the first mixture; preferably 5% to 12%; And / or, drying the agglomerates to remove moisture, and then performing the smelting and reduction reaction to obtain the aluminum-silicon alloy melt; wherein the drying temperature is 120-150° C.; and the moisture content of the agglomerates after drying is less than or equal to 3%; After drying, the agglomerates are smelted and reduced in an electric arc furnace; preferably, the drying temperature is 130-140°C; And / or, the pressure used for making the agglomerates is 30-40 MPa; preferably 30-35 MPa; And / or, the smelting temperature is 2000-2400°C; preferably 2100-2300°C; And / or, the cooling process of the aluminum-silicon alloy melt includes: when the aluminum-silicon alloy melt is cooled to 1200-1400°C, the aluminum-silicon alloy melt is cast in a mold, then cooled to 700-900°C at a rate of 8-12°C / min, kept warm for 50-70 minutes, and finally naturally cooled to 20-35°C to obtain the aluminum-silicon alloy block.
8. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to any one of claims 1 to 7, characterized in that: In the step 3, the filter mud is dried to obtain dry mud; the dry mud, the LiBr, the Al2O3, the TiO2, the MgO and the rare earth oxide are mixed to form the second mixture; the mass proportions of the dry mud, the LiBr, the Al2O3, the TiO2, the MgO and the rare earth oxide in the second mixture are 60-70%, 10-20%, 5-12%, 2-8%, 1-7% and 2-5%, respectively, each substance being calculated on a dry basis; And / or, the rare earth oxide is Eu2O3 or Tb3O4; and / or, the melting treatment temperature of the second mixture is 1350-1600° C., and the melting treatment time is 2-5 hours; And / or, the heat treatment process of the glass body includes primary heat treatment and secondary heat treatment; wherein, the temperature of the primary heat treatment is 500°C to 650°C, and the crystallization time is 0.5 to 2.0 hours; the temperature of the secondary heat treatment is 750°C to 880°C, and the crystallization time is 0.5 to 3.0 hours.
9. The method for preparing silicon-aluminum alloy co-produced luminescent glass by using fly ash and kaolin according to any one of claims 1 to 8, characterized in that: The mass proportions of the dry mud, the LiBr, the Al2O3, the TiO2, the MgO and the rare earth oxide in the second mixture are 60-70%, 10-15%, 5-10%, 3-7%, 2-5% and 3-5% respectively; and / or, the melting treatment temperature of the second mixture is 1400-1530° C., and the melting treatment time is 3-4 hours; And / or, the heat treatment process of the glass body includes primary heat treatment and secondary heat treatment; wherein, the temperature of the primary heat treatment is 600°C to 650°C, and the crystallization time is 0.5 to 1.0 h; the temperature of the secondary heat treatment is 750°C to 800°C, and the crystallization time is 1.5 to 2.5 h.
10. The method for preparing silicon-aluminum alloy and luminescent glass by using fly ash and kaolin as described in any one of claims 1 to 9 obtains silicon-aluminum alloy and luminescent glass; preferably, the luminescent glass is red luminescent glass and green luminescent glass.